The importance of being special: Repo markets during the crisis - Stefano Corradin; Angela Maddaloni (European Central Bank (ECB), 2017)
Specialness - the premium of procuring a specific security in the repo market - increased in the second half of 2011 for Italian government bonds. We assess the impact on specialness of the outright purchase program of the Eurosystem during the same period. Bonds bought by the Eurosystem had higher specialness. The impact was economically significant and persistent. Short-selling traders had to pay a net premium to close their positions and therefore may have decided to fail on their delivery. Indeed bonds that were bought under the program were more likely to be underlying a fail-to-deliver transaction.
Keywords: E43; E51; G01; G12; G23; 330; Repo; Specialness; Central bank asset purchases; Short-selling